Banks' equity stakes in borrowing firms: A corporate finance approach - Jukka Vauhkonen (Bank of Finland, 2003)
In most countries, banks' equity holdings in firms that borrow from then are rather small.In light of the theoretical literature, this is somewhat surprising.For example, according to agency cost models, allowing banks to hold equity would seem to alleviate firms' asset substitution moral hazard problem associated with debt financing.This idea is formalised in John, John, and Saunders in a model where banks are modeled as passive investors and bank loans are the only source of outside finance for firms.In this paper, we argue that this alleged benefit of banks' equity holding is small or non-existent when banks are modeled explicitly as active monitors and firms have access also to market finance.
URN:NBN:fi:bof-20140807158
Keywords: D82; G32; 330; banks' equity holdings; firms' capital structure; social welfare